Ferronematic liquid crystal polymers and elastomers - Reeves, Sarah J. (2022)
Liquid crystal polymers, through covalent bonding, combine the spontaneous long range orientational order of the liquid crystal state with the entropically driven random coil configurations of the skeletal polymer chains in a single material [1]. [...]